Pendidikan Karakter, Kesehatan Fisik dan Mental Siswa Sekolah Dasar Negeri Pesisir - Amrul Hayat; Tito Parta Wibowo; Ahmad Mubarok; Imamudin Imamudin; M. Wandi (Journal of Social Responsibility Projects by Higher Education Forum, 2025)
−Character education, physical health, and mental health are three essential pillars for the holistic development of elementary school students, particularly in coastal areas facing socio-economic, environmental, and educational access challenges. This study analyzes the interrelationship among these aspects using literature review and contextual analysis of coastal regions. The findings indicate that character education integrated into the curriculum and school activities, including physical education, plays a significant role in fostering students’ moral values, ethics, discipline, and social skills. Physical health is influenced by nutrition, physical activity, and environmental conditions, with coastal areas often experiencing malnutrition, limited sports facilities, and poor sanitation and clean water access. Meanwhile, students’ mental health is vulnerable to authoritarian parenting, poverty, natural disasters, and bullying, but can be improved through social support, early detection programs, and resilience building. The analysis reveals a strong reciprocal relationship: good physical health supports mental well-being, character education reinforces healthy lifestyles, and stable mental health facilitates learning and positive character formation. This study recommends a comprehensive Whole School Approach involving teachers, parents, communities, and policymakers to integrate character education with the promotion of physical and mental health in a sustainable manner in coastal schools.